A Delphi-FMEA Framework for Proactive Risk Assessment in Smart Electrical Distribution Networks - Riska Iva Riana; Yan Herdianzah; Nurul Ilmi (Cognitia : International Engineering Journal, 2026)
The adoption of smart grid technologies has improved the efficiency and reliability of electrical distribution systems; however, it has also introduced new operational, environmental, and safety risks that require proactive management. This study aims to develop and implement a Delphi-FMEA framework for risk assessment in the smart electrical distribution network of PT PLN Tello Sector. Data were collected through three Delphi rounds involving eight experts with 16-22 years of professional experience in electrical distribution, maintenance, operations, reliability engineering, and SCADA systems. The Delphi method was used to achieve expert consensus on potential risks, while FMEA was applied to evaluate risk severity, occurrence, and detection, yielding Risk Priority Number (RPN) values for prioritization. The analysis identified 30 potential risks across four main components: network (23%), facilities (23%), inventory (27%), and planning (27%). The most critical risks were inadequate protection against extreme weather conditions (RPN = 270), falls from height due to insufficient safety measures (RPN = 200), and electrical shock during maintenance activities (RPN = 180). Pareto analysis showed that the five highest-priority risks accounted for approximately 44% of the total risk exposure. Root cause analysis revealed that human-related factors accounted for 30% of critical risk causes, followed by equipment (25%), methods (20%), environment (15%), and technology and communication factors (10%). The findings indicate that the Delphi-FMEA framework provides an effective and systematic approach for proactive risk identification and prioritization, supporting improved decision-making, system reliability, operational resilience, and sustainable risk management in smart electrical distribution networks.